Impact of the processes of total testicular regression and recrudescence on the epididymal physiology of the bat myotis nigricans (chiroptera: vespertilionidae) - Beguelini, Mateus R. [UNESP]; Goes, Rejane M. [UNESP]; Rahal, Paula [UNESP]; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastiao R. [UNESP] (Public Library Science, 2015)
Myotis nigricans is a species of vespertilionid bat, whose males show two periods of total testicular regression within the same annual reproductive cycle in the northwest Sao Paulo State, Brazil. Studies have demonstrated that its epididymis has an elongation of the caudal portion, which stores spermatozoa during the period of testicular regression in July, but that they had no sperm during the regression in November. Thus, the aim of this study was to analyze the impact of the total testicular regression in the epididymal morphophysiology and patterns of its hormonal regulation. The results demonstrate a continuous activity of the epididymis from the Active to the Regressing periods; a morphofunctional regression of the epididymis in the Regressed period; and a slow recrudescence process. Thus, we concluded that the processes of total testicular regression and posterior recrudescence suffered by Myotis nigricans also impact the physiology of the epididymis, but with a delay in epididymal response. Epididymal physiology is regulated by testosterone and estrogen, through the production and secretion of testosterone by the testes, its conduction to the epididymis (mainly through luminal fluid), conversion of testosterone to dihydrotestosterone by the 5 alpha-reductase enzyme (mainly in epithelial cells) and to estrogen by aromatase; and through the activation/deactivation of the androgen receptor and estrogen receptor a in epithelial cells, which regulate the epithelial cell morphophysiology, prevents cell death and regulates their protein expression and secretion, which ensures the maturation and storage of the spermatozoa.